2017
DOI: 10.1096/fj.201700438r
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidin trimer gallate modulates lipid deposition and fatty acid desaturation inCaenorhabditis elegans

Abstract: The incidence of obesity is rising at an alarming rate. Despite its recognition as an urgent healthcare concern, obesity remains largely an unsolved medical problem. A comprehensive screen for functional dietary phytochemicals identified proanthocyanidins as putative targets to ameliorate obesity. A full-scale purification of oligomeric proanthocyanidins (OPCs) derived from grape seed extract yielded pure OPC dimer, trimer, tetramer, and their gallates (pOPCs). Forward chemical screening conducted in suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…However, the current result suggests that EGCG reduced the expression of acs-2 in the wild type nematodes, which indicate that EGCG might inhibit fat oxidation although overall fat accumulation was still reduced in C. elegans . Similar discrepancies have been previously reported that low-fat phenotypes might lead to compensatory suppression of acs-2 transcription to prevent further energy expenditure ( 32 ). Thus, we inferred that reduced expression of acs-2 by EGCG has no significance on its effect on overall body fat in this model.…”
Section: Discussionsupporting
confidence: 87%
“…However, the current result suggests that EGCG reduced the expression of acs-2 in the wild type nematodes, which indicate that EGCG might inhibit fat oxidation although overall fat accumulation was still reduced in C. elegans . Similar discrepancies have been previously reported that low-fat phenotypes might lead to compensatory suppression of acs-2 transcription to prevent further energy expenditure ( 32 ). Thus, we inferred that reduced expression of acs-2 by EGCG has no significance on its effect on overall body fat in this model.…”
Section: Discussionsupporting
confidence: 87%
“…In comparison, A-type proanthocyanidins extracted from Cinnamomum tamala increase the concentration of insulin in the blood and pancreas (3). In general, oligomeric proanthocyanidins are thought to be most bioactive in terms of regulating lipid metabolism (4-7), in particular the galloyl ester structure (8)(9)(10)(11). The heterogeneous building blocks and complex linkage patterns of proanthocyanidins make their fractionation and purification challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lu et al (2020) declared that GSPE significantly attenuated the expression of IL-1β. Moreover, Nie et al (2017) found that, trimer gallate of oligomeric proanthocyanidins down-regulated the nuclear hormone receptor-49 (an ortholog of the human PPARα), a key regulator of fat metabolism. Interestingly, the evident reduction of oxidative stress and inflammatory markers as IL-1β by GSPE can be owing to its beneficial effects of scavenging ROS, and increasing the epithelial barrier integrity, and decreasing inflammation (Nallathambi et al, 2020), while as the significant down regulation of PPARα expression in this study may be explained as a positive feedback for alleviating of oxidative stress and inflammation by GSPE.…”
Section: Discussionmentioning
confidence: 99%